DWA GŁOSY O POSTSOWIECKOSCI I POSTKOLONIALIZMIE W EUROPIE ŚRODKOWEJ Cristina Şandru. Worlds Apart? A Postcolonial Reading of post-1945 East-Central European Culture. Newcastle upon Tyne: Cambridge Scholars Publishing, 2013. 309 P. Bogdan Ştefănescu. Postcommunism / Postcolonialism: Siblings of Subalternity. Bucharest: University of Bucharest Publishing House, 2013. 227 P. - Kledzik, Emilia (Porównania, 2015)
DWA GŁOSY O POSTSOWIECKOSCI I POSTKOLONIALIZMIE W EUROPIE ŚRODKOWEJ